Genital infections with Chlamydia trachomatis and Neisseria gonorrhoeae in Ghanaian women. Issue 1 (February 1985) - Bentsi, C; Klufio, C A; Perine, P L; Bell, T A; Cles, L D; Koester, C M; Wang, S P
Abstract : Women who attended the gynaecology clinic or were admitted to the postpartum ward of Korle Bu Hospital, Accra, Ghana were tested for infection with Chlamydia trachomatis and Neisseria gonorrhoeae. Eight (4.9%) of 162 gynaecological patients were infected with C trachomatis and five (3.1%) with N gonorrhoeae, and respective prevalences among 148 postpartum women were 7.7% (3/39) and 3.4% (5/148). Among 40 gynaecological patients who were not pregnant and whose principal complaint was of lower abdominal pain, 4 (10%) were infected with C trachomatis and none with N gonorrhoeae. Antibodies against serovars D, E, F, and G were common, and three typable isolates were serovar G. C trachomatis would appear to be more common than N gonorrhoeae in obstetric and gynaecological patients in Ghana.